Role of Oral and Esophageal Microbiota in Esophageal Squamous Cell Carcinoma - Kong Jinyu; Wang Jian; Liu Yiwen; Li Ruonan; Gao Shegan (Clinical Medicine Insights: Oncology)
In China, esophageal cancer (EC) is one of the most prevalent malignant tumors of the digestive system. EC has a high incidence and mortality rate, of which esophageal squamous cell carcinoma (ESCC) accounts for more than 90%. Due to a lack of effective prevention and treatment methods, the 5 year survival rate is less than 30%. In recent years, microecology has become a hot spot in cancer research, and dysbiosis may play an important role in the etiology of EC. Presently, research on the relationship between the microbiome and ESCC remains in its early stages. This narrative review examines the relationship between the oral and esophageal microbiota and ESCC. A better understanding of this relationship may facilitate early detection and the optimization of treatment strategies.